(untitled) - Rosai, Juan (New York, 2011)
Efficiently review the clinical presentation, gross and microscopic features, ultrastructural and immunohistochemical findings, differential diagnosis, therapy, and prognosis for virtually every pathologic entity. Compare your findings to more than 3,300 outstanding illustrations that capture the characteristic presentation of every type of lesion. Avoid diagnostic pitfalls using Dr. Rosai's expert observations on what to look for, what to be careful about, and which presentations can be misleading. Find quick answers on tumor staging, quality control procedures, and the handling of gross specimens through valuable appendices.
Keywords: Bệnh lý, phẩu thuật,Pathology, surgical